THE EFFECT OF REGISTRATION, E-FILING, AND E-BILLING APPLICATIONS ON TAX PAYER LEVEL SATISFACTION OF TAXPAYER COMPLIANCE AT KPP PRATAMA JOMBANG 2019-2020 - Winoto, Haris Tri Ramadhani; Pudjolaksono, Drs. Eko (UTSAHA: Journal of Entrepreneurship, 2022)
This research investigates the influence of registration, e-Filing, and e-Billing applications on taxpayer satisfaction and their subsequent impact on taxpayer compliance.  Conducted among individual taxpayers registered at KPP Pratama Jombang, the study utilized a sample of 103 respondents.  Data analysis was performed using Partial Least Squares (PLS) with the Smart PLS 3.0 software.  The findings reveal that the registration application significantly affects taxpayer satisfaction, positively impacting taxpayers by eliminating the need for in-person visits to the local KPP for registration, thus saving valuable time previously spent queuing.  Similarly, e-Filing also demonstrates a significant positive effect on taxpayer satisfaction, streamlining and expediting tax return reporting through the DJP application or website, accessible anytime and anywhere.  Conversely, e-Billing does not show a significant effect on taxpayer satisfaction, attributed to a lack of understanding regarding the e-billing system, the distance between taxpayers' residences and payment points like banks, post offices, or ATMs, and the resulting queues and time constraints caused by limited access to these facilities.  Finally, the research indicates that taxpayer satisfaction influences taxpayer compliance, with higher levels of satisfaction correlating with increased compliance.